Interference rejection in wireless digital communications - Hu, Ying. (2008)
In this dissertation, the objective is to investigate interference-rejection schemes which will enhance the system performance over AWGN and fading channels in the presence of narrowband jammer. In this research, a generic direct-sequence spread-spectrum (DS/SS) system is first modeled and analyzed with emphasis on narrowband jammer, additive white Gaussian noise and nonfading environments.